The Sukarno file, 1965-1967 : chronology of a defeat - Dake, A. C. A. (Antonie C. A.) (Social sciences in Asia ;, 2006)
The book gives a detailed and final account of what happened on 1 October 1965 in Jakarta, Indonesia. Six anti-communist Army generals were kidnapped and then murdered. Mid-level officers were involved, as well as the leadership of the Indonesian Communist Party, PKI. Apparent aim was to move the country to the left. The plot failed due to swift action of major-general Suharto, the later President, until then completely unknown even to the CIA. The coup turned out to be a blunder of major proportions resulting in the annihilation of the PKI as organization. When the military found out that Sukarno himself had been behind the conspiracy, he was shunted aside without bringing him to court. Instead of left, the country turned right.